Effects of fiscal consolidation on business confidence in the Euro area - Michail, N.; Savva, Savvas C.; Koursaros, Demetris (My University, 2018)
© 2018, Oviedo University Press. All rights reserved. We employ a factor-augmented VAR (FAVAR) covering both domestic and international developments to examine the confidence effects of a fiscal shock, using a sample of six euro area countries. The results indicate that following a shock in total government expenditure, responses are country-specific, while a weak geographical pattern, i.e. a distinction between core and periphery countries can be observed. Overall, the confidence response is short-lived and returns to zero after a few quarters. Heterogeneity in country responses also indicates that the Bachmann and Sims (2012) conclusion suggesting the endogenous response of confidence can explain almost all of the fiscal-driven output expansion in recessions, may hold only in country-specific cases.